PO133 Neuromyelitis optica spectrum disease preceded by three year history of intermittent gastro-intestinal dysfunction. (1st December 2017) - Maclean, Rory; Everett, Rosie; Slivkova, Ralitsa; Woodhall, Mark; Rifkin-Zybutz, Raphael; Armstrong, Richard; Weir, Andrew; Waters, Patrick; Booth, Michael; Isabel Leite, M
Abstract : A 59-year-old man presented with acute right-sided neck and arm pain which progressed to right arm numbness and profound right hand weakness. On MRI, a longitudinally extensive transverse myelitis affecting the cervical spinal cord with extension into the medulla was seen. He was treated with high-dose IV steroids followed by oral steroids with modest improvement. Aquaporin-4 autoantibody positivity confirmed neuromyelitis optic spectrum disease (NMOSD). Over the previous three years, patient experienced recurrent/three-monthly episodes of abdominal pain, distension, vomiting and hiccups lasting a few days with spontaneous improvement. He was seen multiple times in the gastroenterology and GI Surgery departments. GI investigations, including CT and diagnostic laparoscopy revealed no structural defect. Since commencing immunosuppression, five months ago, he has not experienced further neurological or gastrointestinal episodes. It is well recognised that NMOSD can present with vomiting/nausea/hiccups, but overt bowel involvement has not been described. The medullary lesion involving the dorsal vagal complex might have been the site of recurrent inflammatory episodes, causing pan-gastrointestinal dysfunction. This case illustrates that early presentations of NMOSD can manifest as non-neurological complaints, not recognised to be consequence of nervous system dysfunction until after a more typical presentation, thus thwarting early diagnosis and treatment with accompanying morbidity.